PERAN ORANG TUA DALAM MENINGKATKAN MUTU PENDIDIKAN ANAK USIA DINI KB PELITA HARAPAN REJANG LEBONG - Muhammad Naufal Gustrianto; Miranda Utari; M. Royhan Laverdho; Herdiansyah Herdiansyah (INCARE, International Journal of Educational Resources, 2023)
This study aims to describe the role of parents in improving the quality of PAUD KB Pelita Harapan Rejang Lebong education. This research is motivated by events in the field, that researchers see if students are less qualified in their education, students who have bad morals or have bad manners are blamed for the educators or teachers themselves. Meanwhile, if students who are more successful or those who have good abilities, the honored are the parents of the students themselves. This study uses a qualitative descriptive method, which describes the events in the field as they are. Data collection by researchers is by observation, interviews, and documentation. Based on research conducted by researchers, it can be concluded that parental involvement inearly childhood education must be aligned with various programs and operational efforts that are adjusted to the analysis of various obstacles experienced by parents including social status factors, family form factors, family development stage factors, and factor role models. In addition, the teacher has a synergistic role, because as a school communicator and provides information to students in teaching. Communication with parents/guardians of students must also be established and maintained so that two-way communication can occur.